LEKSIKON KEKERABATAN ETNIK MELAYU BANGKA DI KOTA PANGKALPINANG - Rahmat Muhidin (Balai Bahasa Sumatera Utara, 2019)
This is research aims to identity and classify the kinship lexicon then explain the role and meaning in Bangkanese Malay greetings. The research used descriptive method. The technique used was ethnographical interview. Bangkanese Malay ethnic in communicating either in nuclear family based on matchmaking or bloodline (offspring). That research result showed that the role and meaning of lexicon kinship dislayed that the people considered as close relatitive are family. Family relation is both consanguine and afinal. It is categorized into ego aligned, over ego, and below ego.